Portraits of the city : representations of Dublin in visual art - a thematic case study - Milligan, Kathryn (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 2015)
This thesis examines the representation of Dublin in visual art, as produced by a range of artists working in Ireland during the nineteenth and twentieth centuries. Thematic in its approach, the artists and artworks discussed encompass a broad time period, spanning the period 1821-1966. From the appearance of the city on grand ceremonial occasions, its destruction during periods of warfare and unrest, to the negotiation of personal identity and belonging through a representation of its streets, bridges, and buildings, the information contained within this volume demonstrates how urban life in Ireland’s capital city has captivated artists for decades. Through a discussion and scholarly examination of these artworks, it is shown that the city has been an important subject for artists in Ireland, despite the predominance of the rural landscape in the wider ‘canon’ of Irish art.
Embargo End Date: 2022-01-01
Keywords: History Of Art, Ph.D.; Ph.D. Trinity College Dublin, 2015